Mechanisms of Body Weight Fluctuations in Parkinson’s Disease - Kistner, Andrea; Lhommée, Eugénie; Krack, Paul (Frontiers in Neurology, 2014)
Typical body weight changes are known to occur in PD. Weight loss has been reported in early stages as well as in advanced disease and malnutrition may worsen the clinical state of the patient. On the other hand an increasing number of patients show weight gain under dopamine replacement therapy or after surgery. These weight changes are multifactorial and involve changes in energy expenditure, perturbation of homeostatic control, and eating behavior modulated by dopaminergic treatment. Comprehension of the different mechanisms contributing to body weight is a prerequisite for the management of body weight and nutritional state of an individual PD patient. This review summarizes the present knowledge and highlights the necessity of evaluation of body weight and related factors, as eating behavior, energy intake and expenditure in PD.